Quantitative Risk Evaluation of Adventitious Agents in Heparin - Raedts, John; Kellenbach, Edwin (TH Open, 2023)
Heparin is typically extracted from domestic pigs, which may carry zoonotic adventitious agents. Prion and viral safety cannot be assured by testing the active pharmaceutical ingredient itself; instead for the evaluation of the adventitious agent (i.e., viruses/prions) safety of heparin and heparinoid (e.g., Orgaran or Sulodexide) therapeutics, a risk assessment is required. An approach is presented which provides a quantitative estimation of the worst-case potential residual adventitious agent (i.e., GC/mL or ID50) present in a maximum daily dose of heparin. This estimation is based on the input (determined by prevalence, titer, and amount of starting material to prepare a maximum daily dose) and validated reduction by the manufacturing process, resulting in an estimation of the worst-case potential level of adventitious agent present in a maximum daily dose. The merits of this quantitative, worst-case approach are evaluated. The approach described in this review provides a tool for a quantitative risk evaluation of the viral and prion safety of heparin.
Keywords: heparin; adventitious agents; viral safety; prion safety; virus reduction; prion reduction